Developing Social Skills through Group Counseling Based on Experiential Learning at MTs Negeri 1 Bandar Lampung: Integrating the Values of Religious Moderation - Monica, Mega Aria; Yuberti (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze the effectiveness of experiential learning-based group guidance services in developing students' social skills at State Junior High School (MTs) 1 Bandar Lampung, while integrating the values ​​of religious moderation. The research method used descriptive qualitative research. The research subjects used purposive sampling consisting of five seventh-grade students identified as having difficulties in social skills and a guidance and counseling (BK) teacher who acted as a facilitator of group counseling sessions. Data collection techniques used were structured observation, semi-structured interviews, and documentation (lesson plans and student reflection notes). Data analysis techniques included three stages: data reduction, data presentation, and drawing conclusions. The results showed that students experienced a significant increase in social skills, in line with the principles of Islamic education that emphasize the balance between faith and a harmonious social life. This study provides a practical contribution to the development of guidance and counseling services in Islamic-based schools, particularly in strengthening character education relevant to the context of a multicultural society.